2019
DOI: 10.1007/s10570-018-2220-6
|View full text |Cite
|
Sign up to set email alerts
|

Microsegregating blends of ethyl cellulose and poly(vinyl pyrrolidone): a combined thermo-mechanical and positron annihilation spectroscopy study

Abstract: Polymer blends are a versatile playground for studying phase separation and its effect on the development of morphology and mechanical properties of the resulting materials. Blends obtained from two immiscible polymers, ethyl cellulose (EC) and poly(vinyl pyrrolidone) (PVP), are especially relevant for their practical applications as coatings for pharmaceutical preparations and controlled drug release. Here, films of EC-PVP blends are studied by means of thermal analysis, dynamic-mechanical analysis as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Microstructural analysis revealed that increases in both the free volume hole size and fraction were caused by increasing the ethylcellulose concentration. The combined structural properties of the polymeric blend determine drug permeability and, therefore, drug release properties [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microstructural analysis revealed that increases in both the free volume hole size and fraction were caused by increasing the ethylcellulose concentration. The combined structural properties of the polymeric blend determine drug permeability and, therefore, drug release properties [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In literature; there are several studies about electrospinning of PVP nanofibers [24][25][26][27]. Hovewer there are limited studies about electrospinning optimization with Taguchi experimental design.…”
Section: Introductionmentioning
confidence: 99%